2020
DOI: 10.1111/acem.14108
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient Treatment of Low‐risk Pulmonary Embolism in the Era of Direct Oral Anticoagulants: A Systematic Review

Abstract: Background Clinical guidelines have supported outpatient treatment of low‐risk pulmonary embolism (PE) since 2014, but adoption of this practice has been slow. Direct oral anticoagulant (DOAC) therapy for venous thromboembolism (VTE) is now as common as vitamin K antagonist treatment, but data are sparse regarding outcomes for patients with low‐risk PE treated with DOACs as outpatients. We conducted a systematic review of literature on outcomes of outpatient management for PE, including comparisons to inpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…Consistent with prior studies, we observed that only 1.3% of patients managed as outpatients experienced return visits for bleeding 31 . This was reassuring because the outcomes achieved in clinical trials do not always translate into routine practice.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Consistent with prior studies, we observed that only 1.3% of patients managed as outpatients experienced return visits for bleeding 31 . This was reassuring because the outcomes achieved in clinical trials do not always translate into routine practice.…”
Section: Discussionsupporting
confidence: 88%
“…The evidence underpinning the management of low‐risk PE in the outpatient setting is centered on two randomized controlled trials and several cohort studies 31 . Based on these data, professional societies have recommended outpatient management of PE for these select patients 11,12,32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have previously evaluated these two triaging tools, but most of them were single-arm cohort studies precluding direct comparison of their safety, applicability, and effectiveness. 3 , 4 To our knowledge, only two studies previously compared the sPESI and the Hestia rule. The first one was retrospective, 18 and the other a single-centre observational prospective study where the investigators did not use the triaging tools for decision-making of home treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 However, current evidence is mainly based on cohort studies using different sets of eligibility criteria. 3 , 4 Therefore, controversy persists about the optimal triaging strategy and eligibility criteria for home treatment. 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation